Culture as embodiment : the social tuning of behavior - Voestermans, P. (Paul), 1946-; Verheggen, Theo, 1972- (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
ICulture as Embodiment/i utilizes recent insights in psychology, cognitive, and affective science to reveal the cultural patterning of behavior in group-related practices./ ulliApplies the best of the behavioural sciences to contemporary issues of behavioural cross-fertilizationin global exchange/liliPresents an original theory to be used in the gender and integration debates, about what the acceptance of newcomers from different cultural backgrounds really entails/liliPresents a theory that is also applicable to youth culture and the split in modern society between underclass, modal class, and the elite/liliContains an original approach to the persistence of religion, and relates religious thought to the cognitive capacity of generic belief/li/ul.
Understanding culture -- Inventing culture theory -- A psychological perspective on culture -- Sex: the shaping of sex and gender -- Status: the body of class and organized compliance -- Age: the optimal balance of love and challenge -- Ethnicity: cultural arrests and bicultural competance -- Faith: religion as a man-made order -- A psychology of globalization -- Epilogue.
"Dutch edition published 2007 by Open Universiteit Nederland and Blackwell Publishing Ltd."
Revised edition of the author's Cultuur & lichaam : een cultuurpsychologisch perspectief op patronen in gedrag.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Social psychology; Ethnopsychology; Culture and psychology; PSYCHOLOGY -- Social Psychology; Culture -- Psychological aspects; Ethnopsychology; Social psychology; Electronic books; Electronic books; Electronic books